Molecular Mechanism Of Synthetic Microrna Underlying Chronic Myeloid Leukaemia Cells Proliferation By Targeting The 3’UTR Of ABL1 Component Of The BCR-ABL1 Fusion Gene - Syarifah Faezah Syed Mohamad (Universiti Sains Islam Malaysia, 2025)
Matric" 4191056 (FPSK)